miR-192-2 Regulates the Proliferation and Apoptosis of Ovarian Granulosa Cells by Targeting IGFBP2 in Zhedong White Geese - Size Wang; Chuicheng Zeng; Yue Pan; Zhengyu Zang; Yuanliang Zhang; Shan Yue; Xiuhua Zhao; He Huang (Animals)
The proliferation and apoptosis of ovarian granulosa cells (GC) is critical for follicular development and ovulation, especially for egg-laying performance in female birds. In geese, follicular atrophy is accompanied by follicular GC apoptosis during brooding stages. MicroRNAs are involved in follicular development, atrophy, ovulation, and degeneration. Our previous high-throughput sequencing study of ovaries from laying and brooding geese revealed that miR-192-2 may be involved in follicle growth and development, as well as follicle cell proliferation and apoptosis in geese. To further investigate the effect of miR-192-2 on GC in geese, we screened the target gene of miR-192-2 (IGFBP2) and constructed a miR-192-2 overexpression and interference vector, synthesized a small interfering RNA for IGFBP2. The results showed that after miR-192-2 overexpression, the mRNA and protein expression of proliferation-related genes (PCNA, CDK2, CCND1, and CCND2) were significantly decreased, the mRNA and protein expression of apoptosis-related genes (Caspase3, Caspase8, and Caspase9) were significantly increased, and the mRNA and protein expression of anti-apoptosis gene Bcl-2 were significantly decreased. While the mRNA and protein expressions of PCNA, CDK2, CCND1, and CCND2 were significantly decreased after the downregulation of IGFBP2 expression, the mRNA and protein expressions of Caspase3, Caspase8, and Caspase9 were significantly increased, and the mRNA and protein expression of Bcl-2 was significantly decreased. In conclusion, miR-192-2 inhibited proliferation and promoted apoptosis of follicular GC by targeting IGFBP2 in Zhedong White geese. Apoptosis of GC leads to follicular atresia, which in turn leads to brooding behavior in female geese. Therefore, it is possible to explore inhibiting the expression of miR-192-2 in production to alter the brooding behavior of Zhedong White Geese, thereby improving egg production and economic returns for producers.